Total Bile Acid Concentration in Duodenal Fluid Is a Useful Preoperative Screening Marker to Rule Out Biliary Atresia. Issue 3 (September 2018) - Fukuoka, Tomoya; Bessho, Kazuhiko; Tachibana, Makiko; Satomura, Yoshinori; Konishi, Akiko; Yasuda, Kie; Kimura, Takeshi; Hasegawa, Yasuhiro; Ueno, Takehisa; Miyoshi, Yoko; Ozono, Keiichi
ABSTRACT: Objectives: Duodenal tube test (DTT) is used as a preoperative screening to rule out biliary atresia (BA). In previous reports, DTT was assessed by the color of the duodenal fluid, but there were no quantitative criteria. The aim of this study was to examine the efficacy of DTT based on the total bile acid (TBA) concentration in duodenal fluid. Methods: This is a single-center retrospective study of infants with cholestasis who underwent DTT from 2008 to 2016 at the Osaka University Hospital. The cut-off values of maximum TBA in duodenal fluid (dTBA), dTBA/serum TBA ratio (sTBA), and dTBA/serum gamma-glutamyl transpeptidase (sGGT) ratio were assessed for the accuracy in excluding BA. Results: A total of 37 infants were included in this study; 16 infants with BA and 21 infants with other causes of intrahepatic cholestasis. dTBA demonstrated sensitivity of 100% and specificity of 90.5% with the cut-off value of 16.8 μmol/L. Specificity was further improved to 95.2% with dTBA/sTBA ratio (cut-off value: 0.088) and 100% with dTBA/sGGT ratio (cut-off value: 0.076 μmol/U). DTT could be performed 0.8 ± 1.4 days after admission. Hypoglycemia was developed in 1 infant. Conclusions: DTT evaluated by dTBA, dTBA/sTBA ratio, and dTBA/sGGT ratio had high accuracy to rule out BA and could avoid unnecessary surgery in some infants. Abstract : Supplemental Digital Content is available in the text